A photocatalytic composite material and its preparation method and application

By loading Ag3PO4 and Ag nanoparticles on a metal-organic framework carrier and forming a Z-shaped heterojunction, the problem of photocorrosion of silver phosphate under visible light irradiation is solved, its photocatalytic activity and stability are improved, and the resistance to organic pollution is enhanced. degradation efficiency of substances.

CN115970763BActive Publication Date: 2025-01-24BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310005910.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-04
Publication Date
2025-01-24
Estimated Expiration
2043-01-04

AI Technical Summary

Technical Problem

Silver phosphate is prone to photocorrosion under visible light irradiation, resulting in a decrease in its photocatalytic activity.

Method used

By loading AG3PO4 and AG nanoparticles on the metal organic frame carrier, and forming Z -shaped heterogeneous knots to change the separation and transfer of photocopy, inhibit the AG+light reduction reaction.

Benefits of technology

It effectively inhibits the photocorrosion of silver phosphate, improves its stability and photocatalytic activity, and improves the degradation rate of organic pollutants by increasing the contact area and charge transfer efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115970763B_ABST
    Figure CN115970763B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of photocatalysis technology, and specifically relates to a photocatalytic composite material, a preparation method thereof, and an application thereof. The present invention provides a photocatalytic composite material, comprising a metal organic framework carrier and Ag3PO4 and Ag nanoparticles loaded on the metal organic framework carrier; the metal organic framework carrier and Ag3PO4 form a Z-type heterojunction. The present invention changes the separation and transfer of photogenerated carriers by constructing a Z-type heterojunction between Ag3PO4 and the metal organic framework carrier, thereby being able to inhibit the occurrence of Ag3PO4 photocorrosion, improve the stability of Ag3PO4, and improve the photocatalytic activity of the photocatalytic composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalysis, and in particular relates to a photocatalytic composite material and a preparation method and application thereof. Background Art

[0002] Photocatalytic degradation technology uses semiconductor materials as catalysts. Under light conditions, electrons in semiconductor materials jump from the valence band to the conduction band, generating highly active electron-hole pairs and highly oxidizing free radicals, which can convert organic pollutants into non-toxic carbon dioxide and water, thereby achieving the degradation of organic pollutants.

[0003] Silver phosphate is a semiconductor photocatalyst with a large absorption of visible light and high quantum efficiency under visible light irradiation. However, when silver phosphate is exposed to visible light, Ag + It easily undergoes reduction reaction with electrons to generate metallic Ag, which causes photocorrosion of silver phosphate and reduces the photocatalytic activity of silver phosphate. Summary of the invention

[0004] The purpose of the present invention is to provide a photocatalytic composite material and a preparation method and application thereof. The photocatalytic composite material provided by the present invention can inhibit the photocorrosion of silver phosphate and has excellent photocatalytic activity.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a photocatalytic composite material, comprising a metal organic framework carrier and Ag3PO4 and Ag nanoparticles loaded on the metal organic framework carrier;

[0007] The metal organic framework support and Ag3PO4 form a Z-type heterojunction.

[0008] Preferably, the metal organic framework support comprises MIL-101(Cr).

[0009] Preferably, the mass ratio of the metal organic framework support to Ag3PO4 is 1:1 to 5;

[0010] The mass ratio of the Ag nanoparticles to the metal organic framework carrier is 0.028-0.55:1.

[0011] The present invention also provides a method for preparing the photocatalytic composite material described in the above technical solution, comprising the following steps:

[0012] A soluble silver salt solution and a soluble phosphate solution are sequentially added into a dispersion containing a metal organic framework carrier, and a coprecipitation reaction is carried out under light-proof conditions to obtain the photocatalytic composite material.

[0013] Preferably, the soluble silver salt in the soluble silver salt solution includes silver nitrate and / or silver acetate.

[0014] Preferably, the soluble phosphate in the soluble phosphate solution includes soluble orthophosphate and / or soluble dihydrogen phosphate.

[0015] Preferably, the molar ratio of the soluble silver salt in the soluble silver salt solution to the soluble phosphate in the soluble phosphate solution is 3 to 3.5:1.

[0016] Preferably, the mass ratio of the soluble silver salt in the soluble silver salt solution to the metal organic framework carrier in the dispersion containing the metal organic framework carrier is 1.2 to 6.0:1.

[0017] Preferably, the coprecipitation reaction is carried out under stirring;

[0018] The stirring speed is 600-1000 rpm, and the stirring time is 12-24 hours.

[0019] The present invention also provides the use of the photocatalytic composite material described in the above technical solution or the photocatalytic composite material prepared by the preparation method described in the above technical solution in catalytic degradation of organic pollutants.

[0020] The present invention provides a photocatalytic composite material, including a metal organic framework carrier and Ag3PO4 and Ag nanoparticles loaded on the metal organic framework carrier; the metal organic framework carrier and Ag3PO4 form a Z-type heterojunction. The present invention changes the separation and transfer of photogenerated carriers by constructing a Z-type heterojunction between Ag3PO4 and the metal organic framework carrier. Specifically: under the irradiation of visible light, the electrons in the transport electron conduction band (CB) of Ag3PO4 are easily transferred to the metal Ag fixed at the interface between the metal organic framework carrier and Ag3PO4 through the Schottky barrier, because the CB edge of Ag3PO4 is more negative than the Fermi level of metal Ag. In addition, since the highest occupied molecular orbital (HOMO) of the metal organic framework carrier is more positive than the Fermi level of metal Ag, the holes in the HOMO of the metal organic framework carrier will also be transferred to the metal Ag; since the electrons on the CB of Ag3PO4 are basically consumed, the Ag is reduced. + The photoreduction of Ag3PO4 is inhibited, thereby inhibiting the occurrence of Ag3PO4 photocorrosion and improving the stability of Ag3PO4. At the same time, the electrons on the metal organic framework carrier accumulate at the lowest unoccupied molecular orbital (LUMO), and the holes remain in the transport hole valence band (VB) of Ag3PO4, which can generate a large amount of ·OH and ·O2 -Free radicals can further improve the photocatalytic activity of the photocatalytic composite material; in addition, due to the large specific surface area of ​​the metal organic framework carrier, the contact area between Ag3PO4 and organic pollutants can be effectively increased, which can further improve the photocatalytic rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 XRD patterns of the photocatalytic composite materials obtained in Examples 1 to 3, MIL-101(Cr) obtained in Example 1, and pure Ag3PO4;

[0022] Figure 2 This is the SEM image of pure Ag3PO4;

[0023] Figure 3 is the SEM image of MIL-101(Cr) in Example 2;

[0024] Figure 4 This is a SEM image of the photocatalytic composite material obtained in Example 2;

[0025] Figure 5 HRTEM image of the photocatalytic composite material obtained in Example 2;

[0026] Figure 6 This is the full XPS spectrum of the photocatalytic composite material obtained in Example 2;

[0027] Figure 7 Ag3dXPS spectra of the photocatalytic composite materials and pure Ag3PO4 obtained in Examples 1 to 3;

[0028] Figure 8 The UV-visible absorption spectra of the photocatalytic composite material obtained in Example 2, MIL-101 (Cr) in Example 2 and pure Ag3PO4;

[0029] Fig. 9 The (αhν)2~hν curve diagram of the photocatalytic composite material obtained in Example 2, MIL-101(Cr) in Example 2 and pure Ag3PO4;

[0030] Fig.10 The photocatalytic efficiency diagram of the photocatalytic composite material obtained in Examples 1 to 3, MIL-101 (Cr) in Example 2 and pure Ag3PO4 as photocatalysts;

[0031] Fig.11 This is a photocatalytic efficiency diagram after four degradation tests using the photocatalytic composite material obtained in Example 2 and pure Ag3PO4 as photocatalysts;

[0032] Fig.12The XRD diagrams before and after four degradation tests using the photocatalytic composite material obtained in Example 2 as a photocatalyst;

[0033] Fig.13 Schematic diagram of the photocatalytic mechanism of the photocatalytic composite material when the metal organic framework carrier is MIL-101(Cr). DETAILED DESCRIPTION

[0034] The present invention provides a photocatalytic composite material, comprising a metal organic framework carrier and Ag3PO4 and Ag nanoparticles loaded on the metal organic framework carrier;

[0035] The metal organic framework support and Ag3PO4 form a Z-type heterojunction.

[0036] In the present invention, the metal organic framework support preferably includes MIL-101(Cr).

[0037] In the present invention, the Ag nanoparticles act as a charge transfer bridge to transfer electrons between the metal organic framework carrier and Ag3PO4.

[0038] In the present invention, the MIL-101(Cr) is preferably obtained by preparation; the preparation method preferably comprises the steps of:

[0039] The soluble chromium salt, terephthalic acid, hydrofluoric acid and water are mixed and subjected to a hydrothermal reaction to obtain the MIL-101(Cr).

[0040] In the present invention, unless otherwise specified, all raw materials are commercially available products well known to those skilled in the art.

[0041] In the present invention, the soluble chromium salt preferably includes chromium nitrate. In a specific embodiment of the present invention, the chromium nitrate is preferably added in the form of chromium nitrate nonahydrate. In the present invention, the molar ratio of the soluble chromium salt, terephthalic acid and water is preferably 1:1:222-389, and more preferably 1:1:278. In the present invention, the molar ratio of terephthalic acid and hydrofluoric acid is preferably 1:0.5-2, and more preferably 1:1.

[0042] In the present invention, the mixing is preferably carried out under stirring and ultrasonic conditions. The present invention has no particular limitation on the stirring and ultrasonic process, as long as the raw materials can be mixed uniformly.

[0043] In the present invention, the temperature of the hydrothermal reaction is preferably 200-220°C, more preferably 210°C; the time is preferably 8-14h, more preferably 9-13h, more preferably 10-12h. In the present invention, the hydrothermal reaction is preferably carried out in a hydrothermal reactor.

[0044] After the hydrothermal treatment is completed, the present invention also preferably includes post-treatment of the obtained product; the post-treatment preferably includes cooling, removing impurities, purifying, washing, filtering and drying in sequence.

[0045] In the present invention, the cooling method is preferably natural cooling to room temperature.

[0046] In the present invention, the impurity removal process preferably includes: filtering the liquid obtained after cooling through a G2 funnel and a G4 funnel in sequence to obtain a green powder. In the present invention, unreacted terephthalic acid can be removed by impurity removal.

[0047] In the present invention, the purification process preferably comprises:

[0048] The green powder and N,N-dimethylformamide are first mixed, and then subjected to ultrasonic treatment and filtration to obtain a precipitate;

[0049] The precipitate is mixed with ethanol for a second time and subjected to solvothermal treatment.

[0050] The present invention has no particular limitation on the amount of N,N-dimethylformamide added and the first mixing process, and those skilled in the art can use methods well known to those skilled in the art. In the present invention, the temperature of the ultrasonic treatment is preferably 80° C., and the time is preferably 1 hour. The present invention has no particular limitation on the filtering process, and those skilled in the art can use methods well known to those skilled in the art.

[0051] The present invention has no particular limitation on the amount of ethanol added and the second mixing process, and those skilled in the art may adopt the process known to those skilled in the art. In the present invention, the temperature of the solvent thermal treatment is preferably 80° C., and the time is preferably 24 hours.

[0052] In the present invention, the washing method is preferably hot ethanol. The present invention has no special limitation on the washing and filtering process, and the washing and filtering process can be performed by a process well known to those skilled in the art.

[0053] In the present invention, the drying temperature is preferably 150° C. In the present invention, the drying is preferably performed under vacuum conditions.

[0054] In the present invention, the mass ratio of the metal organic framework support to Ag3PO4 is preferably 1:1-5, more preferably 1:2-4, and more preferably 1:3.

[0055] The present invention also provides a method for preparing the photocatalytic composite material described in the above technical solution, comprising the following steps:

[0056] A soluble silver salt solution and a soluble phosphate solution are sequentially added into a dispersion containing a metal organic framework carrier, and a coprecipitation reaction is carried out under light-proof conditions to obtain the photocatalytic composite material.

[0057] In the present invention, the soluble silver salt in the soluble silver salt solution preferably includes silver nitrate and / or silver acetate.

[0058] In the present invention, the soluble phosphate in the soluble phosphate solution includes soluble orthophosphate and / or soluble dihydrogen phosphate.

[0059] In the present invention, the soluble orthophosphate preferably includes sodium orthophosphate and / or potassium orthophosphate. In the present invention, the soluble dihydrogen phosphate preferably includes potassium dihydrogen phosphate and / or sodium dihydrogen phosphate.

[0060] In the present invention, the molar ratio of the soluble silver salt in the soluble silver salt solution to the soluble phosphate in the soluble phosphate solution is preferably 3 to 3.5:1. The present invention has no particular limitation on the concentrations of the soluble silver salt solution and the soluble phosphate solution, and those known to those skilled in the art may be used. In a specific embodiment of the present invention, the concentration of the soluble silver salt solution is preferably 0.3 mol / L; the concentration of the soluble phosphate solution is preferably 0.1 mol / L.

[0061] In the present invention, the mass ratio of the soluble silver salt in the soluble silver salt solution to the metal organic framework carrier in the dispersion containing the metal organic framework carrier is preferably 1.2 to 6.0:1, more preferably 2.0 to 5.0:1, and more preferably 3.6:1. The present invention does not specifically limit the concentration of the dispersion containing the metal organic framework carrier, and the concentration familiar to those skilled in the art can be adopted. In a specific embodiment of the present invention, the mass concentration of the metal organic framework carrier in the dispersion containing the metal organic framework carrier is preferably 1 to 9 g / L, specifically 1.672 g / L, 2.78 g / L or 8.36 g / L.

[0062] In the present invention, the dispersion containing the metal organic framework carrier is preferably prepared by; the preparation method preferably comprises the following steps:

[0063] The metal organic framework carrier and water are mixed and subjected to ultrasonic treatment to obtain the dispersion containing the metal organic framework carrier.

[0064] The present invention has no particular limitation on the mixing process, and any method known to those skilled in the art may be used. In the present invention, the ultrasonic treatment time is preferably 30 minutes.

[0065] In the present invention, the adding method is preferably dropwise addition; the dropwise addition speed is preferably 1 to 3 s / drop. In the present invention, the dropwise addition is preferably performed under stirring conditions. The present invention has no particular limitation on the stirring process, and the stirring process known to those skilled in the art can be used.

[0066] In the present invention, the coprecipitation reaction is carried out under light-proof conditions.

[0067] In the present invention, the coprecipitation reaction is preferably carried out under stirring; the stirring speed is preferably 600-1000 rpm, more preferably 700-900 rpm; the time is preferably 12-24 h, more preferably 15-22 h, more preferably 18-20 h.

[0068] After the coprecipitation reaction is completed, the present invention also preferably includes filtering, washing and drying the obtained product in sequence.

[0069] In the present invention, the filtering method is preferably centrifugal; the centrifugal speed is preferably 3500r / min. In the present invention, the washing preferably includes deionized water washing and ethanol washing in sequence. In a specific embodiment of the present invention, the number of deionized water washing is preferably 3 times, and the number of ethanol washing is preferably 3 times.

[0070] In the present invention, the drying temperature is preferably 60° C., and the drying time is preferably 8 to 12 hours. In the present invention, the drying is preferably performed under vacuum conditions.

[0071] The present invention also provides the use of the photocatalytic composite material described in the above technical solution or the photocatalytic composite material prepared by the preparation method described in the above technical solution in catalytic degradation of organic pollutants. The present invention has no special limitation on the specific implementation of the application, and it can be carried out in a manner familiar to those skilled in the art.

[0072] In the present invention, when the metal organic framework carrier is MIL-101 (Cr), the schematic diagram of the catalytic mechanism of the photocatalytic composite material is as follows: Fig.13As shown, specifically: In the Ag / Ag3PO4 / MIL-101(Cr) photocatalyst system, Ag nanoparticles can act as a charge transfer bridge to accept holes from the HOMO of MIL-101(Cr) and electrons from the CB of Ag3PO4, thereby forming a Z-type charge transfer system. The formed Z-type transmission channel can promote the transmission of photogenerated charges and maintain a strong redox potential. On the other hand, Ag helps to quickly transfer electrons from the CB of Ag3PO4 to MIL-101(Cr), and can also act as an "electron sink" to store electrons. In addition, the plasma surface resonance effect (SPR) of Ag nanoparticles can increase the visible light absorption capacity of the composite material. At the same time, the electrons on MIL-101(Cr) can reduce dissolved O2 to ·O2 - . h on VB of Ag3PO4 + Reacts with H2O to generate ·OH. In addition, the h + It can also directly attack organic pollutants. Therefore, the photocatalytic composite material provided by the present invention has multiple charge transfer channels (one is Z-type charge transfer; the other is the SPR effect of Ag nanoparticles), which can promote the separation of photogenerated charge carriers and the generation of active free radicals, thereby improving the photocatalytic performance of the photocatalytic composite material.

[0073] In order to further illustrate the present invention, a photocatalytic composite material provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0074] Example 1

[0075] 4.0 g Cr(NO3)3·9H2O, 1.66 g terephthalic acid, 0.4 mL hydrofluoric acid and 50 mL deionized water were mixed and uniformly mixed under stirring and ultrasonic conditions; the obtained mixture was placed in a hydrothermal reactor, heated to 220°C for hydrothermal reaction, and kept warm for 8 hours; after naturally cooling to room temperature, the obtained liquid was filtered through a G2 funnel and a G4 funnel in turn to remove unreacted terephthalic acid to obtain a green powder; the green powder was mixed with N,N-dimethylformamide, and ultrasonically treated at 80°C for 1 hour, and after filtering, the obtained precipitate was mixed with ethanol and solvent thermally treated at 80°C for 24 hours; the obtained product was washed with hot ethanol, heated to 150°C under vacuum conditions and dried overnight to obtain MIL-101(Cr);

[0076] 0.418 g of MIL-101 (Cr) was mixed with 50 mL of deionized water and ultrasonically treated for 30 min to obtain a dispersion containing MIL-101 (Cr); then, 10 mL of a 0.3 mol / L AgNO3 solution and 10 mL of a 0.1 mol / L Na2HPO4·12H2O solution were sequentially added dropwise to the dispersion containing MIL-101 (Cr) at a dropping speed of 2 s / drop under stirring; the obtained mixed solution was then stirred at 800 rpm for 24 h in a light-proof condition for a co-precipitation reaction; after the reaction was completed, the obtained feed liquid was centrifuged at 3500 r / min, and the obtained precipitate was washed three times with deionized water and three times with ethanol in turn, and then heated to 60°C and dried for 12 h under vacuum conditions to obtain a photocatalytic composite material (denoted as AAM-1).

[0077] Example 2

[0078] 0.139 g of MIL-101 (Cr) obtained in Example 1 was mixed with 50 mL of deionized water and ultrasonically treated for 30 min to obtain a dispersion containing MIL-101 (Cr); then, 10 mL of a 0.3 mol / L AgNO3 solution and 10 mL of a 0.1 mol / L Na2HPO4·12H2O solution were sequentially added dropwise to the dispersion containing MIL-101 (Cr) at a dropping speed of 2 s / drop under stirring; the obtained mixed solution was then stirred at a speed of 800 rpm for 24 h in a light-proof condition for a co-precipitation reaction; after the reaction was completed, the obtained feed liquid was centrifuged at a speed of 3500 r / min, and the obtained precipitate was washed three times with deionized water and three times with ethanol in turn, and then heated to 60°C and dried for 12 h under vacuum conditions to obtain a photocatalytic composite material (denoted as AAM-3).

[0079] Example 3

[0080] 0.0836 g of MIL-101 (Cr) obtained in Example 1 was mixed with 50 mL of deionized water and ultrasonically treated for 30 min to obtain a dispersion containing MIL-101 (Cr); then, 10 mL of a 0.3 mol / L AgNO3 solution and 10 mL of a 0.1 mol / L Na2HPO4·12H2O solution were sequentially added dropwise to the dispersion containing MIL-101 (Cr) at a dropping speed of 2 s / drop under stirring; the obtained mixed solution was then stirred at a speed of 800 rpm for 24 h in a light-proof condition for a co-precipitation reaction; after the reaction was completed, the obtained feed liquid was centrifuged at a speed of 3500 r / min, and the obtained precipitate was washed three times with deionized water and three times with ethanol in turn, and then heated to 60°C and dried for 12 h under vacuum conditions to obtain a photocatalytic composite material (denoted as AAM-5).

[0081] Performance Testing

[0082] Test Example 1

[0083] The photocatalytic composite materials obtained in Examples 1 to 3, the MIL-101 (Cr) obtained in Example 1 and pure Ag3PO4 were subjected to X-ray diffraction test, and the obtained XRD patterns are as follows: Figure 1 shown; from Figure 1 It can be seen that the MIL-101 (Cr) obtained in Example 1 has a high degree of crystallinity, showing major diffraction peaks at 25.2, 8.5, 9.1, 10.3 and 16.5; all diffraction peaks of pure Ag3PO4 completely correspond to the body-centered cubic structure of Ag3PO4 (JCPDS No. 060505);

[0084] In addition, the diffraction peak at 38.1° in the XRD patterns of AAM-3 and AAM-5 matches the (111) reflection peak of metallic silver (JCPDS No. 04-0783), proving the presence of Ag nanoparticles.

[0085] The photocatalytic composite materials provided by the present invention all show characteristic peaks of MIL-101(Cr) and Ag3PO4, indicating that the composite materials have been successfully prepared. In addition, as the amount of MIL-101(Cr) introduced increases, the diffraction peak intensity of the MIL-101(Cr) phase in the composite material gradually increases, while the diffraction peak intensity of the Ag3PO4 phase decreases. In addition, no change in the characteristic peak position of MIL-101(Cr) is observed in the photocatalytic composite material, indicating that the crystal structure of MIL-101(Cr) is not destroyed after the introduction of Ag3PO4.

[0086] Test Example 2

[0087] The photocatalytic composite material obtained in Example 2, MIL-101 (Cr) in Example 2 and pure Ag3PO4 were detected by scanning electron microscopy, and the obtained SEM images are as follows: Figures 2 to 4 As shown, Figure 2 For pure Ag3PO4, Figure 3 MIL-101(Cr), Figure 4 The photocatalytic composite material obtained in Example 2; Figures 2 to 4 It can be seen that pure Ag3PO4 is agglomerated particles composed of irregular particles with uneven particle size and an average particle size of about 200-300nm; MIL-101(Cr) shows a typical octahedral structure with an average size of 800nm; Example 2 shows that Ag3PO4 nanoparticles in the photocatalytic composite material are attached to MIL-101(Cr), indicating that Ag3PO4 and MIL-101(Cr) are effectively combined;

[0088] The photocatalytic composite material obtained in Example 2 was examined by transmission electron microscopy, and the obtained HRTEM image is as follows: Figure 5 As shown, from Figure 5 It can be seen that in the photocatalytic composite material obtained in Example 2, lattice fringes of 0.270 nanometers can be clearly seen, which is equivalent to the (210) crystal plane of the Ag3PO4 component, and lattice fringes of 0.236 nanometers, which is equivalent to the (111) crystal plane of metallic Ag. This shows that metallic silver and Ag3PO4 coexist in the composite material. In addition, it can be clearly observed that the two phases of MIL-101 (Cr) and Ag3PO4 are in close contact and form a close interface, which is conducive to the charge transfer between MIL-101 (Cr) and Ag3PO4, and may promote effective photogenerated electron-hole separation.

[0089] Test Example 3

[0090] The photocatalytic composite material obtained in Example 2 was subjected to X-ray photoelectron spectroscopy detection, and the obtained XPS full spectrum was as follows: Figure 6 As shown, from Figure 6 It can be seen that Cr, Ag, P, C, and O elements are present in the photocatalytic composites;

[0091] The Ag3d XPS spectra of the photocatalytic composite materials obtained in Examples 1 to 3 and pure Ag3PO4 are shown in Figure 2. Figure 7 As shown, from Figure 7 It can be seen that in the Ag3d high-resolution spectrum of Ag3PO4, there are two obvious peaks at binding energies of 373.7 and 367.7 eV, which are from Ag3d 5 / 2 and Ag3d 3 / 2 The signal indicates that Ag3PO4 is Ag +Compared with Ag3PO4 alone, the Ag3d 3 / 2 and Ag3d 5 / 2 The positive shift of the Ag3d peak strongly proves the generation of AAM heterojunction, which indicates the intensive electronic interaction and intra-interface contact between Ag3PO4 and MIL-101(Cr). In addition, there are two weak peaks in the composites, which indicates the presence of trace amounts of metallic silver, which is consistent with the results of XRD and HRTEM.

[0092] Test Example 4

[0093] The photocatalytic composite material obtained in Example 2, MIL-101 (Cr) in Example 2 and pure Ag3PO4 were tested by UV-visible diffuse reflectance spectroscopy, and the obtained curve graph is as follows: Figures 8-9 As shown, Figure 8 is the UV-visible absorption spectrum. Fig. 9 For the (αhν)2~hν curve, Figures 8-9 It can be seen that the absorption wavelength of the photocatalytic composite material provided by the present invention moves to a longer wavelength, and the absorption intensity is significantly enhanced compared with MIL-101 (Cr) and pure Ag3PO4. The enhanced absorption in the visible light range helps to utilize photons, thereby improving the photocatalytic performance. The band gaps of MIL-101 (Cr), Ag3PO4 and AAM-3 are calculated to be 2.40 eV, 2.45 eV and 2.36 eV respectively using the transformed Kubelka-Munk function.

[0094] Test Example 5

[0095] The photocatalytic performance of the photocatalytic composite materials obtained in Examples 1 to 3, MIL-101 (Cr) in Example 2 and pure Ag3PO4 were verified as photocatalysts:

[0096] Weigh 50 mg of the photocatalyst and disperse it in 100 mL of an aqueous solution containing tetracycline (concentration of 20 mg / L). In order to achieve adsorption-desorption equilibrium, the mixed solution was stirred in the dark for 0.5 hour before illumination. Subsequently, the mixed solution was irradiated with a 300W xenon arc lamp (CEL-HXF300, Perfectlight, China) with a cutoff filter (λ>420 nm). 3 mL of the solution was taken out at given time intervals, and the resulting solution was then filtered with a 0.45 μm polyethersulfone (PES) membrane and analyzed at 357 nm by a UV-visible spectrophotometer. The test graph obtained is as shown below. Fig.10 As shown, from Fig.10It can be seen that almost no obvious degradation was observed in the blank experiment, indicating that the autophotolysis involved in tetracycline was negligible in the absence of a photocatalyst;

[0097] The photocatalytic performance of pure MIL-101(Cr) was poor, and the removal rate of tetracycline was only 33.5% within 60 min of irradiation.

[0098] Pure Ag3PO4, under the same conditions, the removal rate of tetracycline was 70.5%;

[0099] The photocatalytic composite materials provided by the present invention all show higher photocatalytic activity and faster degradation rate. In particular, AAM-3 shows the highest photocatalytic activity, and the removal rate of tetracycline after irradiation for 60 minutes is 97.9%. The good photocatalytic activity of the Ag / Ag3PO4 / MIL-101(Cr) composite material is attributed to the formation of a heterojunction between Ag3PO4 and MIL-101(Cr), and the Ag nanoparticles serve as a charge transfer bridge in the middle, which can promote the effective separation of photogenerated charge carriers during the reaction process. Loading Ag3PO4 in MIL-101(Cr) can form more active sites for photocatalytic reactions. However, with the continuous increase of the Ag3PO4 content, excessive Ag3PO4 loading may lead to agglomeration, and the area exposed to the incident light will be reduced, resulting in a decrease in activity.

[0100] Test Example 6

[0101] Verify the stability of the photocatalytic composite material provided by the present invention:

[0102] The photocatalytic composite material obtained in Example 2 and pure Ag3PO4 were subjected to a tetracycline degradation test according to the method in Test Example 5. The degradation test was repeated four times, and the degradation efficiency diagram obtained was as shown in FIG. Fig.11 As shown, from Fig.11 It can be seen that the photocatalytic composite material provided by the present invention still maintains a high degradation efficiency after 4 cycles;

[0103] After the degradation test of the photocatalytic composite material obtained in Example 2 was repeated four times, an X-ray diffraction test was performed, and the obtained XRD pattern was as follows: Fig.12 As shown, from Fig.12 It can be seen that the structure of the photocatalytic composite material provided by the present invention is basically the same after 4 degradation tests and before use.

[0104] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A photocatalytic composite material, characterized in that: It comprises a metal organic framework carrier and Ag3PO4 and Ag nanoparticles loaded on the metal organic framework carrier; The metal organic framework support and Ag3PO4 form a Z-type heterojunction; The metal organic framework carrier is MIL-101 (Cr).

2. The photocatalytic composite material according to claim 1, characterized in that: The mass ratio of the metal organic framework support to Ag3PO4 is 1:1-5; The mass ratio of the Ag nanoparticles to the metal organic framework carrier is 0.028-0.55:

1.

3. The method for preparing the photocatalytic composite material according to claim 1 or 2, characterized in that: The following steps are involved: A soluble silver salt solution and a soluble phosphate solution are sequentially added into a dispersion containing a metal organic framework carrier, and a coprecipitation reaction is carried out under light-proof conditions to obtain the photocatalytic composite material.

4. The preparation method according to claim 3, characterized in that: The soluble silver salt in the soluble silver salt solution includes silver nitrate and / or silver acetate.

5. The preparation method according to claim 3, characterized in that: The soluble phosphate in the soluble phosphate solution includes soluble orthophosphate and / or soluble dihydrogen phosphate.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The molar ratio of the soluble silver salt in the soluble silver salt solution to the soluble phosphate in the soluble phosphate solution is 3 to 3.5:

1.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the soluble silver salt in the soluble silver salt solution to the metal organic framework carrier in the dispersion containing the metal organic framework carrier is 1.2 to 6.0:

1.

8. The preparation method according to claim 3, characterized in that: The coprecipitation reaction is carried out under stirring; The stirring speed is 600-1000 rpm, and the stirring time is 12-24 hours.

9. Use of the photocatalytic composite material according to claim 1 or 2 or the photocatalytic composite material prepared by the preparation method according to any one of claims 3 to 8 in catalytic degradation of organic pollutants.